The Ecumenical Response to Disability: The World Council of Churches - Kabue, Sam (Journal of religion, disability & health, 2006)
Since the late 1960s, disability issues have been on the agenda of the World Council of Churches. Emerging from its Faith Order Commission as a theological examination of disability in light of the compassion of Christ, the various forms of action have raised the conscience of member communions and the WCC organization. The ministry has taken many forms depending on financial and other resources. Its most recent forum, EDAN (Ecumenical Disability Advocates Network) has held consultations around the globe and has developed an interim theological statement „A Church of All and For All.”